Analysis of The Efficiency and Effectiveness of Regional Financial Management in the Regional Revenue Management Agency of Asahan Regency - Dwi Septialamsyah; Juliana Nasution (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2022)
One of the important in regional autonomy and decentralisastion is a problem regional financial management and budget, for that efficiencyand effectiveness of financial management required to finance the government work, development, and social service community. This research to analyze do income and regional spending in Badan Pengelola Pendapatan Daerah Kabupaten Asahan has been implemented efficiency and effectively. The method of analysis that used is descriptive analysis. The results of the study based on guidelines assessment and financial performance in Badan Pengelola Pendapatan Daerah Kabupaten Asahan as whole, the average level of the effectiveness of regional financial management in Badan Pengelola Pedapatan Daerah Kabupaten Asahan during fiscal year 2017 up to 2021 expressed effective. It showed government pervormance in realizing local revenue based on potential real religion in 2017until 2021 is good. While overall, the average level of efficiency in the management of their financing ini Badan Pengelola Pendapatan Daerah Kabupaten Asahan during fiscal year 2017 up to 2021 it will be said inefficient because regional spending remained high if in comparison to the total regional income. Should Badan Pengelola Pendapatan Daerah Kabupaten Asahan  optimize to collect local revenue and for local governments have a priority scale in the determination of budget spending